Critically Assessing Mechanisms for The Protection of Workers Against Unfair Dismissal in Cameroon - Tangwa Modestine Ginje (Zien Journals, 2021)
The ILO in order to bring to an end the concept of “at will” termination which was the practice in most countries adopted, the Termination of Employment Convention No 158 of 1982. The aim of this Convention was to do away with unfair dismissal situations which existed in most countries. Irrespective of the existence of the above Convention, the practice of determination of contracts of employment in Cameroon is employer -friendly as the employer is free to determine(terminate) the contract of his employee for a cause or no reason at all. This principle runs in contradiction with the ILO Convention No 158 of 1982, a treaty duly ratified by Cameroon which provides in Article 4 for termination based on a valid reason. Though there exist several structures such as the Labour inspectorate which are in place to ensure the protection of workers against unfair termination, unfair termination has remained a pertinent issue in the Cameroon economy. This is premise on the fact that the mechanisms put in place to afford protection to workers has failed to live up to expectation.
Keywords: Termination of Employment Contract; Protection; Determination; work